A review of telemedicine in accident and emergency: the story so far. Issue 3 (1st May 2000) - Benger, Jonathan
Abstract : Recent developments in information and communications technology have the potential to revolutionise health care. This has been recognised at government level, and plays a significant part in the new information strategy for the NHS " Information For Health ". Telemedicine (literally, medicine at a distance) is one of the most successful techniques in this rapidly expanding field, and in preliminary studies has proved to be both successful and popular with patients and health care professionals. In the UK telemedicine has been mainly applied to two major areas of accident and emergency (A&E) practice. These are the transmission of computed tomography scans for urgent neurosurgical opinion and the ongoing support of minor injuries units. The latter also involves transmission and interpretation of radiographs, usually peripheral limb films. Telemedicine is not a medical sub-specialty in itself, but a facilitator of all medical and surgical specialties. While recent modernisation initiatives have permitted A&E departments to purchase a range of telemedical equipment, overall progress is hampered by a lack of large or scientifically rigorous studies, and a complete absence of data on the economic implications of this new technique. This review introduces A&E telemedicine in terms that avoid jargon and complex technical details. After a brief consideration of the origins of the subject, attention is given to recent publications relating to minor injuries support and A&E teleradiology. The technical and clinical feasibility of A&E telemedicine are demonstrated, and a case is made for the transmission and interpretation of minor injuries radiographs using a relatively simple and inexpensive system, supported by timely radiological reporting. After a brief study of various legal and ethical issues, the likely developments of the future are discussed.